2009
DOI: 10.1108/14757700911006976
|View full text |Cite
|
Sign up to set email alerts
|

Capital structure and firm characteristics: an empirical analysis from Egypt

Abstract: PurposeThe aim of this paper is to investigate differences in capital structures across industries in Egypt paying particular attention to: corporate characteristics, such as liquidity, asset structure, growth, and size; fiscal characteristics, namely, the application of differential corporate tax rates; and stock market activity.Design/methodology/approachComparisons are made between the four main industrial sectors: food, heavy industries, contracting and services. For each industry four aspects of capital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 21 publications
4
29
0
5
Order By: Relevance
“…Therefore, we partially accept the hypothesis number 1, which states that: There is a significant relationship between the firm's tangibility and capital structure of the firm expressed by leverage ratio. Similarly, this relationship was demonstrated by previous SME studies such as Hall et al (2004) and Cassar and Holmes (2003 large Egyptian companies reached a quite similar conclusion (Omran and Pointon, 2009). These past reviews demonstrated a positive relationship between utilization of Long-term liabilities and tangibility, recommending that the tangible asset is the important determinant of access to outside fund for SMEs.…”
Section: Results Of Hypotheses Testingsupporting
confidence: 86%
See 4 more Smart Citations
“…Therefore, we partially accept the hypothesis number 1, which states that: There is a significant relationship between the firm's tangibility and capital structure of the firm expressed by leverage ratio. Similarly, this relationship was demonstrated by previous SME studies such as Hall et al (2004) and Cassar and Holmes (2003 large Egyptian companies reached a quite similar conclusion (Omran and Pointon, 2009). These past reviews demonstrated a positive relationship between utilization of Long-term liabilities and tangibility, recommending that the tangible asset is the important determinant of access to outside fund for SMEs.…”
Section: Results Of Hypotheses Testingsupporting
confidence: 86%
“…Meanwhile, it was positively significant with total leverage and short term leverage of the second sample and insignificant with the long term leverage. The results of the second sample are consistent with results of Aybar-Arias et al (2012), Hall et al, (2000), Omran and Pointon (2009 ) and the assumption of Myers and Majluf (1984), who concluded that the growing companies would need outside finance.…”
Section: Growth and Leverage Ratiosupporting
confidence: 89%
See 3 more Smart Citations